2022
DOI: 10.1155/2022/2164974
|View full text |Cite
|
Sign up to set email alerts
|

Intraday Price Discovery between Spot and Futures Markets of NIFTY 50: An Empirical Study during the Times of COVID‐19

Abstract: The current study investigates the intraday dynamics of futures and spot markets in India. By analyzing one-minute data of Nifty 50 and the associated futures index, the study finds that both the markets are cointegrated. The results of the VECM reveal that any disequilibrium between the spot and futures market is restored by the spot market. Granger causality tests reveal that the spot and futures markets have a bidirectional causal relationship. Common factor weights and Hasbrouck’s information share (IS) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The results of this study are in line with various studies that found futures markets often lead spot markets in price discovery 14,17,26 . This study uses monthly data of India's benchmark equity futures and spot prices over an extended time period from April 2005 to December 2022.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are in line with various studies that found futures markets often lead spot markets in price discovery 14,17,26 . This study uses monthly data of India's benchmark equity futures and spot prices over an extended time period from April 2005 to December 2022.…”
Section: Discussionsupporting
confidence: 91%
“…Hou et al (2019) observe a time-varying volatility spillover between fuel oil and stock index futures markets, while Zhou et al (2021) note bidirectional spillovers between stock index futures and spot prices influenced by news releases. Khan et al (2022)26 explore the intraday dynamics of India's Nifty 50 futures and spot markets, and they find two-way volatility spillovers with futures having a greater impact. They use the Baba, Engle, Kraft, and Kroner (BEKK) -Generalized Autoregressive Conditional Heteroskedasticity (GARCH) also known as BEK-GARCH model, Granger causality tests, common factor weights, and Hasbrouck's IS to support their findings Qin et al (2023).…”
mentioning
confidence: 99%
“…Technology adoption has been referred to as "a complex, inherently social, developmental process." The adoption process is not only influenced by external factors but cognitive, emotional and contextual aspects also influence the process [32]. The review of prior studies on technology adoption forms the basis of theoretical foundation and formulation of hypotheses for the present study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, programs and measures have been put in place to effectively support both environmental sustainability and financial development [ 9 ]. Nevertheless, the results reported for these programs are not reliable, and research that does not take the composite risk index into account offers conflicting conclusions about environmental measures [ 10 ]. Investigating these issues and providing environmental, economic, and policy-oriented recommendations that pertain to both the economy and the environment are therefore crucial tasks [ 11 ].…”
Section: Introductionmentioning
confidence: 99%